The Effect of Agricultural Infrastructure Policies on Rice Production in Indonesia - Ifani, Ifani; Sartiyah, Sartiyah; Ernawati, Ernawati (Lafadz Jaya Publisher, 2024)
The purpose of this study is to analyze how government policies related to agricultural facilities and infrastructure have an impact on rice production in Indonesia. This study uses panel data from 34 provinces in Indonesia observed for 8 years from 2015 to 2022. Maximum Likelihood (M) Robust Least Square Method (RLS) regression method was used in this study. The results showed that all variables studied, namely extension, irrigation development, reservoir development, tractor assistance, and subsidized fertilizer, had a positive impact on rice production in Indonesia. Therefore, to achieve food security and improve the economy of farmers, the government must continue and develop these agricultural policies.